Effects of growing and uncontrolled urbanization in the northern region of Salta and Vaqueros in Argentina - López, Emilce de las Mercedes (Universidad Antonio Nariño, 2021)
The city of Salta and the municipality of Vaqueros have shown a significant demographic growth over the last fewdecades, a growth that constitutes a threat to the region’s quality of water. By means of analyzing current existingdata, the article illustrates the effect that recent and uncontrolled urbanization has had on microbiological, physical and chemical quality of subterranean water through time. Accordingly, the variables selected were the presence of pathogenic microorganisms (coliform bacteria) and nitrate concentration in water, the latter being the most frequent pollutant of underground aquifers. It concludes that the relation between the increase of nitrate concentration and population growth is due to contamination caused by septic tanks, hence, the implementation of sewer systems and water treatment plants should be considered promptly, as well as a thorough land usage plan to control the growth of urban areas in the regionfocus of this study.